Immigration and schooling : redefining the 21st century America - Somé, Touorizou Hervé; Orelus, Pierre W. (Critical constructions., 2015)
At the time of Obama's draconian anti-immigrant policies leading to massive deportation of undocumented, poor immigrants of color, there could not be a more timely and important book than this edited volume, which critically examines ways in which immigration, race, class, language, and gender issues intersect and impact the life of many immigrants, including immigrant students. This book documents the journey, many success-stories, as well as stories that expose social inequity in schools and U.S. society. Further, this book examines issues of social inequity and resource gaps shaping the relations between affluent and poor-working class students, including students of color. Authors in this volume also critically unpack anti-immigrant policies leading to the separation of families and children. Equally important, contributors to this book unveil ways and degree to which xenophobia and linguicism have affected immigrants, including immigrant students and faculty of color, in both subtle and overt ways, and the manner in which many have resisted these forms of oppression and affirmed their humanity. Lastly, chapters in this much-needed and well-timed volume have pointed out the way racism has limited life chances of people of color, including students of color, preventing many of them from fulfilling their potential succeeding in schools and society at large.